Thermal behavior of phenol-furfuryl alcohol resin/carbon nanotubes composites - Conejo, L. S. [UNESP]; Costa, M. L. [UNESP]; Oishi, S. S.; Botelho, E. C. [UNESP] (IOP Publishing, 2018)
Phenol-furfuryl alcohol resins (PFA) are excellent candidates to replace existing thermoset matrices used in obtaining insulating systems or carbon materials, both in its pure form and reinforced with nanoscale structures. This work had as main purpose synthesize and investigate thermal characterization of PFA resin and its nanostructured composites with different concentrations of carbon nanotubes (0, 0.1, 0.5 and 1.0 wt%). The DSC analysis was performed to estimate the specific heat (cp) of the cured samples and thermomechanical analysis to find the linear thermal expansion coefficient (α). From these results, the cp values found for the PFA system was similar to that described in the literature for the phenolic resin. The cp increased with the increase in the CNT concentration in the system up to 0.5%. The coefficient of linear thermal expansion obtained by TMA technique for PFA sample was 33.10-6/°C which was close to the α value of phenolic resin (40 to 80.10-6/°C).
Keywords: carbon nanotubes; linear thermal expansion coefficient; nanocomposites; phenol-furfuryl alcohol resin; specific heat